The invasive legume Lupinus polyphyllus has minor site-specific impacts on the composition of soil bacterial communities - Mousavi, Seyed Abdollah (Wiley-Blackwell, 2025)
Plant invasions can have major impacts on ecosystems, both above- and belowground. In particular, invasions by legumes, which often host nitrogen-fixing symbionts (rhizobia), are known to modify soil bacterial communities. Here, we examined the effect of the invasive herbaceous legume Lupinus polyphyllus on the alpha diversity and community composition of soil bacteria. We also explored the relationships between these bacterial communities and vegetation cover, the cover of other (non-invasive) legumes, or the number of vascular plants present. For this, we sampled rhizosphere soil and surveyed vegetation from ten paired sites (uninvaded versus invaded more than 10 years ago) in southwestern Finland, and identified bacterial DNA using 16S rRNA gene amplicon sequencing. The presence of the plant invader and the three vegetation variables considered had no effect on the alpha diversity of soil bacteria in terms of bacterial richness or Shannon and Inverse Simpson diversity indices. However, the composition of soil bacterial communities differed between invaded and uninvaded soils at four out of the ten sites. Interestingly, the relative abundances of the top bacterial families in invaded and uninvaded soils were inconsistent across sites, including for legume-associated rhizobia in the family Bradyrhizobiaceae. Other factors—such as vegetation cover, legume cover (excluding L. polyphyllus), number of plant species—also explained a small proportion of the variation in bacterial community composition. Our findings indicate that L. polyphyllus has the potential to modify the composition of local soil bacterial community, at least in sites where it has been present for more than a decade.